Effects of taper parameters on free spectral range of non‐adiabatic tapered optical fibers for sensing applications. Issue 4 (April 2016) - Musa, B.; Mustapha Kamil, Y.; Abu Bakar, M. H.; Noor, A. S. M.; Ismail, A.; Mahdi, M. A.
ABSTRACT: We investigated the effects of taper parameters on the free spectral range of transmission spectrum of non‐adiabatic tapers. From experimental results, the optimum profile for the tapered fiber in terms of taper angle, waist diameter, and length are 11.500 mrad, 10 μm, and 20 mm, respectively. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:798–803, 2016